2009
DOI: 10.1590/s0100-69162009000200002
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidade espacial de atributos físicos de um argissolo vermelho-amarelo sob pastagem e vegetação secundária em regeneração natural

Abstract: Este trabalho foi realizado com o objetivo de estudar a variabilidade espacial de atributos físicos de um Argissolo Vermelho-Amarelo sob pastagem e vegetação secundária em regeneração natural. Duas áreas foram escolhidas em uma encosta, com a amostragem de solo à profundidade de 0-0,2 m, com os pontos georreferenciados em uma malha regular de 10x10 m, totalizando 64 pontos em cada área. Foram avaliados o volume total de poros, macroporosidade, microporosidade, densidade do solo, resistência do solo à penetraçã… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0
11

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 10 publications
3
7
0
11
Order By: Relevance
“…The frequency distribution was normal for bulk density at depth 2 (Table 1), similar to the data found by Lima et al (2007), and tending towards normal for density at 1 m deep, whereas Lima et al (2009),Cavallini et al (2010, Martins et al (2009) andRosa Filho et al (2009) observed normality in these attributes at both depths. The mean values for bulk density at depths 1 and 2 showed a marked difference (1.59 and 1.54 kg/dm 3 , respectively), while maximum values showed a greater interval (1.89 and 1.76 kg/dm 3 , respectively).…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The frequency distribution was normal for bulk density at depth 2 (Table 1), similar to the data found by Lima et al (2007), and tending towards normal for density at 1 m deep, whereas Lima et al (2009),Cavallini et al (2010, Martins et al (2009) andRosa Filho et al (2009) observed normality in these attributes at both depths. The mean values for bulk density at depths 1 and 2 showed a marked difference (1.59 and 1.54 kg/dm 3 , respectively), while maximum values showed a greater interval (1.89 and 1.76 kg/dm 3 , respectively).…”
Section: Resultssupporting
confidence: 81%
“…The remaining physical attributes of the soil showed medium variability. In general, the coefficients of variation for attributes bulk density (BD) and mechanical resistance to penetration (RP) were in the same range as those described by Lima et al (2009), Lima et al (2007 and Colet et al (2009), whereas the OM level was higher than those reported by Cavalcante et al (2007) and Cavallini et al (2010), obtained at the same location.…”
Section: Resultssupporting
confidence: 49%
“…Os valores indicaram que todos os atributos estudados apresentaram dependência espacial, que é expressa por meio dos ajustes aos modelos de semivariogramas, com exceção para as variáveis silte e microporosidade, no manejo de cana-de-açúcar, e a variável argila, no manejo de mandioca, que apresentaram efeito pepita puro, sendo esse parâmetro encontrado por Lima et al (2007). O efeito pepita indicou a variabilidade não explicada em razão da distância de amostragem utilizada (Souza et al, 2006).…”
Section: Resultsunclassified
“…O conhecimento da variabilidade espacial dos atributos do solo é fundamental, a fim de minimizar os erros de amostragem e o manejo do solo (Lima et al, 2007). Segundo Souza et al (2009), isso só é possível com o uso de técnicas geoestatísticas, que possibilitam a interpretação dos resultados, com base na estrutura da variabilidade natural dos atributos.…”
Section: Introductionunclassified
“…Different spatial dependence characteristics were observed among the treatments. Therefore, different managements may have changed the spatial variability of the soil attributes, indicating that the spatial variability of a particular physical attribute depends not only on factors of soil formation but also on the management adopted, as emphasized by LIMA et al (2009).…”
Section: Resultsmentioning
confidence: 99%